2002
DOI: 10.1046/j.1524-4741.2002.08606.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Women With Metastatic Breast Cancer

Abstract: We examined sleeping problems in women with metastatic breast cancer in relation to depression, social support, and salivary cortisol. Ninety-seven women with metastatic breast cancer were drawn from a larger study on the effects of group therapy on quality of life and survival. This study is based on the baseline assessments conducted prior to randomization into treatment conditions. Sleep, depression symptoms, and social support were assessed by self-reporting. Cortisol was assessed from saliva samples taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
106
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 29 publications
12
106
1
9
Order By: Relevance
“…Of particular concern is the possibility that there may be profound consequences of disturbed sleep for cancer patients, because sleep may mediate both psychologic health and physical health. 38,41,42 In fact, sleep disturbances have been associated with worse quality of life in cancer patients, including increased depression and higher pain levels, 40,43 and with depression in noncancer patients. 42 Persistent sleep disturbances also may increase a cancer patient's risk for mood disorders, altered metabolic and endocrine function, and compromised immune functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern is the possibility that there may be profound consequences of disturbed sleep for cancer patients, because sleep may mediate both psychologic health and physical health. 38,41,42 In fact, sleep disturbances have been associated with worse quality of life in cancer patients, including increased depression and higher pain levels, 40,43 and with depression in noncancer patients. 42 Persistent sleep disturbances also may increase a cancer patient's risk for mood disorders, altered metabolic and endocrine function, and compromised immune functioning.…”
Section: Discussionmentioning
confidence: 99%
“…42 Persistent sleep disturbances also may increase a cancer patient's risk for mood disorders, altered metabolic and endocrine function, and compromised immune functioning. 38,41,43,44 It is noteworthy that sleep disruptions have been associated with adverse physical health outcomes, including increased morbidity and mortality. [45][46][47] Potential changes in metabolic, endocrine, and immune function may have particularly important health consequences for patients with hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Hann and colleagues (Hann et al, 1999) reported adequate internal consistency for this scale in both healthy controls (alpha=.87) and cancer patients (alpha =.89) and good test-retest reliability in both healthy controls (r= 0.51;p < 0.001) and cancer patients (r = 0.57; p < 0.001). The measure has one sleep-related item ("My sleep was restless") and is similar in this way to other depression scales (e.g., Zung Depression Inventory (Zung, 1965); BDI (Beck, 1978))Pain-In keeping with previous research in our laboratory concerning pain among women with metastatic breast cancer (e.g., Koopman, Nouriani et al, 2002;Spiegel & Bloom, 1983)), current pain was assessed using a single item from the Pain Questionnaire (Spiegel & Bloom, 1983): "Please rate your experience of pain at this moment by selecting a number from 1 "not noticeable" to 10 "excruciating -worst ever".Stressful life events-Stressful life events were measured using a 37-item checklist developed by Horowitz, Schaefer, Hiroto, Wilner and Levin (Horowitz, Schaefer, Hiroto, Wilner, & Levin, 1977). This assessment was conducted only at baseline.…”
mentioning
confidence: 88%
“…Koopman and colleagues (Koopman, Nouriani et al, 2002) found that 63% of a sample of metastatic breast cancer patients reported one or more types of sleep disturbance. In a sample of 72 breast cancer patients, Fortner and colleagues (2002) found that 61% had significant sleep deficits.…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation